(untitled) (AL MUNAZHZHARAH, 2021)
The ideal marriage is a marriage that is able to achieve the goal of marriage to become a sakinah, mawaddah and rahmah family. The Qur’an and as-Sunnah do not explain in detail about the age limit for marriage. There are two perspectives regarding the age limit for marriage in Indonesia, first, the perspective of Islamic law, secondly Article 7 Paragraph (1) of Law No. 16 of 2019. Research that answers two problem formulations, namely: What is the Minimum Age Limit for Marriage in Article 7 Paragraph (1) of the Law NO 16 of 2019 ? What is the minimum age limit for Maqasidus Shariah marriage? and the purpose of this research is to find out the study of the minimum age limit for marriage in Article 7 Paragraph (1) of Law No. 16 of 2019 from the Maqasyidus Syariah Perspective. The type of research used is library research. With a qualitative approach, it intends to understand the study of what is in the research subject. The data obtained from the literature is reduced so as to find the main themes and patterns that are relevant to the research. The results of this study are where in Article 7 Paragraph (1) of Law No. 16 of 2019 women can marry at the age of 19 and men at the age of 19. And the ideal age of marriage in the sharia maqasidus perspective is not determined but at the age that is considered to have been able to realize the objectives of the marriage law (maqasidus sharia) such as: creating a sakinah mawaddah wa rahmah family, maintaining lineage, maintaining family relationship patterns, maintaining diversity and being seen as ready in terms of economic, medical, psychological, social, religious aspects. So this perspective will be congruent and single-minded.